Rethinking The Religious Moderation through Intellectual History’s Lens: Mentifact, Sociofact, and Artefact - Titis Thoriquttyas; Ahmad Munjin Nasih; Achmad Sultoni (Institute of Research and Community Service UIN Prof. K.H. Saifuddin Zuhri, 2023)
It must be admitted that there is indeed much research related to religious moderation, but there needs to be more research, especially when it comes to intellectual history discourse. As a contextual discourse, intellectual history still needs sufficient study space among Indonesian academics. Therefore, this study uses an intellectual history perspective to examine religious moderation discourse. Strengthening the study, the authors use the thoughts of Koentjaraningrat and Julian Huxley, who use an anthropological scientific lens to view the discourse of religious moderation. This research is the form of a literature review using the results of research related to intellectual history and the two figures as primary reference sources. Collecting data was carried out by re-reading the text, compiling it, and formulating it to analyze the mentifact, sociofact, and artefact aspects of the discourse of religious moderation. This research produces an academic offer to strengthen the epistemological structure of the discourse of religious moderation by dissecting it through these three dimensions, namely mentifact, sociofact, and artefact. The findings of this research offer the hierarchical relationship on the epistemological of religious moderation (the high ideas, the intermediate ideas, and the lower ideas).